2024
DOI: 10.1038/s41593-024-01576-9
|View full text |Cite|
|
Sign up to set email alerts
|

Blood–brain barrier disruption and sustained systemic inflammation in individuals with long COVID-associated cognitive impairment

Chris Greene,
Ruairi Connolly,
Declan Brennan
et al.

Abstract: Vascular disruption has been implicated in coronavirus disease 2019 (COVID-19) pathogenesis and may predispose to the neurological sequelae associated with long COVID, yet it is unclear how blood–brain barrier (BBB) function is affected in these conditions. Here we show that BBB disruption is evident during acute infection and in patients with long COVID with cognitive impairment, commonly referred to as brain fog. Using dynamic contrast-enhanced magnetic resonance imaging, we show BBB disruption in patients w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 73 publications
1
8
0
1
Order By: Relevance
“…Our central finding is BBB impairment as assessed by the DCE-derived metric K-trans. To the best of our knowledge, there is only one other study that has used K-trans to measure the BBB integrity in PASC ( 4 ). It also showed diffuse BBB impairment at four months post COVID-19 infection but change over the subsequent months was not examined ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our central finding is BBB impairment as assessed by the DCE-derived metric K-trans. To the best of our knowledge, there is only one other study that has used K-trans to measure the BBB integrity in PASC ( 4 ). It also showed diffuse BBB impairment at four months post COVID-19 infection but change over the subsequent months was not examined ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one other study that has used K-trans to measure the BBB integrity in PASC ( 4 ). It also showed diffuse BBB impairment at four months post COVID-19 infection but change over the subsequent months was not examined ( 4 ). Subtle BBB disruption cannot be identified on routine MR studies with gadolinium administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pertinently, COVID-19, particularly in moderate and severe disease, is associated with thrombosis and thrombolytic events, mainly mediated by neutrophils and monocytes [16]. Dysregulation of the coagulation system has been associated in a transcriptomic analysis with disruption of the blood-brain barrier in individuals with neurological symptoms of PASC, including brain fog and cognitive impairment, in association with systemic inflammation [17]. In addition, it has been observed that even a mild respiratory infection of SARS-CoV-2 can induce a persistent inflammatory response in the brain, supported by the CCL11 cytokine, leading to prolonged activation of microglia in subcortical and hippocampal regions, impairing neurogenesis and myelination [18].…”
Section: Post-acute Sequelae Of Sars-cov-2mentioning
confidence: 99%